2016
DOI: 10.1155/2016/3754213
|View full text |Cite
|
Sign up to set email alerts
|

Trimester- and Assay-Specific Thyroid Reference Intervals for Pregnant Women in China

Abstract: Objective. The guidelines of the American Thyroid Association (ATA) recommend an upper limit reference interval (RI) of thyroid stimulating hormone (TSH) of 2.5 mIU/L in the first trimester of pregnancy and 3.0 mIU/L in subsequent trimesters, but some reported ranges in China are significantly higher. Our study aimed to establish trimester- and assay-specific RIs for thyroid hormones in normal pregnant Chinese women. Methods. In this cross-sectional study, 2540 women with normal pregnancies (first trimester, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
2
15
1
2
Order By: Relevance
“…Whereas, the calculated reference ranges for FT 3 concentration in pregnant women (3.40-5.64 pmol/l) was marginally wider than that for non-pregnant women ( and the reference ranges for FT 3 concentration in pregnant and non-pregnant women were narrower than manufacturer's values (3.1-6.5 pmol/l). Factors such as exclusion criteria, population characteristics, immunometric assay method and iodine sufficiency status might have led to different values of such markers [38]. Previous studies [39][40][41] suggested the transformation of the results to multiples of median (MoM) in order to unitize different laboratories reports.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, the calculated reference ranges for FT 3 concentration in pregnant women (3.40-5.64 pmol/l) was marginally wider than that for non-pregnant women ( and the reference ranges for FT 3 concentration in pregnant and non-pregnant women were narrower than manufacturer's values (3.1-6.5 pmol/l). Factors such as exclusion criteria, population characteristics, immunometric assay method and iodine sufficiency status might have led to different values of such markers [38]. Previous studies [39][40][41] suggested the transformation of the results to multiples of median (MoM) in order to unitize different laboratories reports.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of gestational diabetes mellitus and preeclampsia were negatively correlated with maternal free thyroxine (FT4) levels [ 5 ]. Also confusing is the level of thyroid hormones during pregnancy can change markedly and show a significant difference compared with those of nonpregnant people [ 6 , 7 ]. The 2017 Guidelines of the American Thyroid Association (ATA) for the Diagnosis and Management of Thyroid Disease during Pregnancy and the Postpartum have detailed the influence of increase in renal iodine excretion, thyroxine binding proteins, thyroid hormone production, and human chorionic gonadotropin (hCG) on thyroid function in the pregnant women [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the 2017 Guidelines, the ATA pointed out that the extent of TSH reduction varies significantly between different racial and ethnic groups and recommended that each institution or region should establish their own population-based and trimester-specific reference ranges [ 8 ]. However, in China, most of the reference values of thyroid hormones currently used for pregnant women are provided by foreign assay manufacturer for normal adults [ 7 ]. And there is no specialized reference data applied in Zhuang people.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in China it has been shown that prevalence of subclinical hypothyroidism using laboratory trimester specific ranges for TSH was 4% in pregnant women during the first trimester whereas this prevalence was 27.8% when a diagnostic criterion of TSH > 2.5 mU/L was used [21]. Moreover, many reported trimester-specific reference intervals for TSH were different from those recommended by 2011 ATA guidelines [22] [23]. It is therefore probable that, in our study, hypothyroidism frequency determined following 2011 ATA guidelines was overestimated.…”
Section: Discussionmentioning
confidence: 99%